Rapid faults detection for controlling multi-terminal high voltage DC grids under AC grid contingencies - Xu, Z.; Wei, Zhen; Zhang, C. (Elsevier, 2016)
To control power flow for integration of distributed energy onto urban power grids, rapid and accurate detection of the amplitude, phase-angle, and frequency offset of the grid voltage's positive and negative sequence components especially under grid fault conditions are more significant. This paper presents a new faults detection method that is capable of tracking signal deviations on the grid-voltage accurately and rapidly even in the case that bus-voltage contains high order harmonics and random noises. The experimental results verify the validity of the proposed method under various grid-fault conditions.